Investigating the adaptive coping mechanisms of rewilded elephants: A comparison of behavioural and physiological variables with wild elephants - Tenisha Roos; Tamara Eggeling; Marion Garai; Victoria L. Boult; Andre Ganswindt; Brett Mitchell; Audrey Delsink (PLoS ONE, 2026)
Literature on the adaptability and environmental processing abilities of ex-captive (rewilded) African elephants ( Loxodonta africana ) is sparse, emphasising the importance of this research area. By broadening our knowledge on the topic of rewilded elephant behaviour, we can generate a realistic expectation for stakeholders wanting to secure locations for these captive elephants with the aim of rewilding them. We studied 11 African elephants who have been rewilded onto various fenced reserves in South Africa. We measured their adaptability and response to their environment by comparing their behavioural frequencies within four categories and their physiological responses (faecal glucocorticoid metabolite (fGCM) concentrations), to those observed for free-roaming elephants in South Africa. All study animals were grouped into three age/sex categories (Adult females (AF); Adult males (AM); Sub-adult females (SAF)). The results demonstrated that rewilded elephants expressed similar behavioural frequencies to their wild counterparts, except within the “Attentive” category, where both rewilded AMs and SAFs showed significantly lower frequencies than wild elephants. On the contrary, rewilded AFs and SAFs had comparatively higher fGCM concentrations than wild elephants. Through individual comparisons, it was evident that rewilded elephants have adopted unique mechanisms to process environmental stimuli. When the relationship between behavioural and physiological responses was investigated, certain rewilded elephants showed a strong relationship between the two parameters. However, for other elephants, there was no clear correlation between behavioural frequencies and fGCM concentrations. These distinctive differences might largely be influenced by personality traits that will determine whether the elephants respond actively or passively to their environment. This study has shown that rewilded elephants can adapt to wild environments after long-term captivity and that each of them implemented unique ways of coping with both natural and management-related pressures in the different reserves.